The Heterogeneity of Neutrophil Recruitment in the Tumor Microenvironment and the Formation of Premetastatic Niches - Xin Xing; Yongrui Bai; Jian Song (Journal of Immunology Research)
The recruitment of neutrophil to the primary cancer has been shown to be steered by neoplastic cells or tumor-educated mesenchymal stromal cells and has a prometastatic effect. However, the neutrophil chemotaxis and their interaction with tumor cells in the distal metastasized tissues remain elusive. In this review, we discussed emerging research on the interaction between neutrophil recruitment and tumor metastasis, which is essential for studying tumor cell invasion and related immunotherapy.